Influence of Motivation and Confidence on Employee Performance at Mercure Hotel Kota Padang - Akvaro, Habibullah; Abrian, Youmil (Jurnal Pendidikan Tambusai, 2021)
This research is motivated by several problems found by the author. The purpose of this study is to find out the Influence of Motivation and Confidence on Employee Performance at Mercure Padang Hotel. This type of research is classified as quantitative descriptive research with causal associative methods. The types of data used in this study are primary and secondary data. The results of this study showed that the motivation variable in mercure padang hotel was in the good category of 88.68%. As for the confidence variable lies in the unfavorable category of 49.05% and for the employee performance variable is in the good category which is 53.77%. Based on the results of hypothesis testing using multiple linear regression analysis, adjusted R Square value of 0.109, meaning the influence of motivation variables (X1) and confidence (X2) on employee performance variables (Y) by 10.9% while 89.1% is determined by other factors. Furthermore, the results of the double linear regression analysis obtained the value F calculated 7.422 with sig. 0.001 < 0.05, meaning that the motivation variable and confidence in employee performance variables significantly affect.